2011
DOI: 10.1007/s10461-010-9879-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stressful Life Events on Unprotected Anal Intercourse Among Gay and Bisexual Men

Abstract: We investigated the hypothesis that gay and bisexual men experiencing stressful life events are more likely to engage in risky sexual behavior. Data were from a cohort study of 155 HIV-positive and 207 HIV-negative men in Ontario, Canada (1998-2007). We quantified the relation between stressful life events and unprotected anal intercourse with a non-regular partner. In the past 6 months, 19% reported unprotected intercourse (HIV+: 28%; HIV-: 13%) and 58% reported one or more stressful life events (HIV+: 64%; H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…While previous studies in the USA have produced mixed results regarding the negative impact of stressful life events (Calzavara et al, 2012), to the best of our knowledge, this is the first study that has shown an inverse association between stressful life events and sexual risk among MSM. While further exploration of this finding is necessary, occurrence of a particular life event does not measure the extent of its impact on an individual.…”
Section: Discussionmentioning
confidence: 61%
“…While previous studies in the USA have produced mixed results regarding the negative impact of stressful life events (Calzavara et al, 2012), to the best of our knowledge, this is the first study that has shown an inverse association between stressful life events and sexual risk among MSM. While further exploration of this finding is necessary, occurrence of a particular life event does not measure the extent of its impact on an individual.…”
Section: Discussionmentioning
confidence: 61%
“…These various types of violence and stigma may increase MSM vulnerability and difficulty to control their own risk of acquiring HIV [23]–[25]. Studies in North America and sub-Saharan Africa have shown that MSM reporting social discrimination due to their sexual behavior or orientation are more likely to engage in high-risk sex [11], [26]. This study highlights the need for structural interventions addressing frequent human rights violations that can increase risk-taking behaviors and hinder access to prevention and care for MSM in Cote d′Ivoire.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-related risk behaviors such as multiple male and female sexual partnerships and frequent unprotected anal intercourse have been reported among MSM in African countries such as Namibia, Botswana, Malawi, Rwanda and Nigeria [8][10]. In addition, in predominantly hetero-normative sub-Saharan Africa, MSM generally suffer from high stigma, violence, and other human rights violations that can reinforce vulnerability, risky sexual behavior and thus HIV risk [7], [11].…”
Section: Introductionmentioning
confidence: 99%
“…LGBTQ+ individuals face markedly elevated psycho-social stress, including systematic stigmatization, and have higher rates of HIV-risk behaviors (alcohol, substance abuse, unsafe sexual behaviors) [4] , [5] . As a result, they bear a disproportionate burden of Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) and HIV/AIDS-related co-infections [6] .…”
mentioning
confidence: 99%